2019
DOI: 10.1186/s12872-019-1053-z
|View full text |Cite
|
Sign up to set email alerts
|

Acute changes in morphology and renal vascular relaxation function after renal denervation using temperature-controlled radiofrequency catheter

Abstract: BackgroundResistant hypertension and renal sympathetic hyperactivity are closely linked, and catheter-based renal denervation (RDN) is regarded as a new treatment strategy. However, the acute changes in vascular morphology and relaxation function have yet to be evaluated, and these may be important for the efficacy and safety of the procedure. In this study, we explored these questions by conventional temperature-controlled cardiac radiofrequency catheter-based RDN in a pig model.MethodsSix mini-pigs were rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 37 publications
2
5
0
Order By: Relevance
“…We have found no difference in the expression of TH between the animal groups. This finding is in line with a previous report showing that no significant TH expression decrease can be found shortly after RDN, and this might be explained by a delayed axonal degeneration in the necrotic nerves [20]. In the latter study, the authors stated that the level of TH expression cannot reflect the effectiveness of RDN in the acute phase.…”
Section: Renal Artery Stimulationsupporting
confidence: 91%
“…We have found no difference in the expression of TH between the animal groups. This finding is in line with a previous report showing that no significant TH expression decrease can be found shortly after RDN, and this might be explained by a delayed axonal degeneration in the necrotic nerves [20]. In the latter study, the authors stated that the level of TH expression cannot reflect the effectiveness of RDN in the acute phase.…”
Section: Renal Artery Stimulationsupporting
confidence: 91%
“…Our data indicated that eliminating the overactivated renal afferent and efferent sympathetic nervous in renal arteries by RDN significantly reduced SBP and DBP when compared with sham group. Some studies have shown that radiofrequency ablation energy targeting removing sympathetic nervous applied to the arterial wall induced transmural tissue coagulation and loss of endothelium in an acute phase, and transmural media damage coexisted with the presence of proteoglycan at 6 months after RDN [6,7,27]. Vascular endothelial cell injury can cause abnormal proliferation and migration, induce the change from a contractile phenotype to a synthetic phenotype of VSMCs, cause vascular wall thickening, and eventually lead to hypertension and atherosclerosis, which is a lipid-initiated, progressive, inflammatory intimal disease [28].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some studies have been conducted in clinical and preclinical animal models to assess the safety of the procedure, yet some problems, such as a short observation period, limited research scope including renal function, imaging and morphology of renal artery, exist [4][5][6]. The effects of the RDN procedure on the renal artery still need further study because radiofrequency energy is delivered transmurally and can cause vascular wall injury, which may cause endothelial dysfunction and result in an imbalanced release of an increased level of the endothelium-derived relaxation factor nitric oxide (NO) and a decreased level of the endothelium-derived constriction factor endothelin-1 (ET-1), thereby increasing the risk of atherosclerosis [7]. In addition, studies suggest a number of mechanisms of atherosclerosis, including the thrombosis theory, lipid infiltration theory, damage reaction hypothesis, oxidative stress hypothesis, immune dysfunction hypothesis, homocysteine hypothesis and inflammatory reaction theory [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Data from our team's previous studies suggest that intima-RDN may induce or trigger renal artery injury or stenosis. [1][2][3][4] Therefore, similar to the opinion of Dr. Donatella Schiavone and colleagues, even if intima-RDN can control blood pressure, it is not worth promoting.…”
mentioning
confidence: 97%
“…6,7 Although the antihypertensive mechanism of adventitia-RDN remains unclear, several basic studies from our team and others' have preliminarily explored the feasibility and effectiveness of adventitia-RDN. [1][2][3][4] According to investigations, the mechanisms to consider may involve: (1) The severance of the sympathetic nerve distributed around the renal artery in the process of blunt separation of the renal artery and the exposure of its adventitia; (2) The removal of a part of the renal peripheral adipose tissue, thus reducing its influence in secreting unknown substances, secreted by adipocytes, on the sympathetic nerves; and (3) The reduction in sympathetic neurotransmitter release in the renal artery as adventitia-RDN is more conducive than intima-RDN, as shown by a study, which illustrated the renal sympathetic nerve being mainly distributed in the adventitia of the renal artery. 8 Regarding the inclusion criteria, we complied with the American Heart Association definition of resistant hypertension.…”
mentioning
confidence: 99%